Bibliometric analysis of nearly a decade of research in electric vehicles: a dynamic approach (2018)
A bibliometric study was developed based publications of investigation in electric vehicle from 2007 to 2016 available in the science citation Index-expanded database from Web of science, the information was identified in the version on line of SCI-Expanded, Web Thomson Reuters of Science, supported in addition on a powerful tools of information processing like Hitscite. The extracted files were analyzed to determine the number of citations, including publications by year, language, country or region, Journals, articles and authors in order to determine the evolution of this field of study.